Heat-resistant strong adhesive and preparation method thereof
Through the alternative phenolic resin to cross -cross the interface with epoxy oxide, and adding a decorative nano -silicon dioxide, preparing the heat -resistant strong adhesive, solving the problem of insufficient heat resistance and stability of existing phenolic resin adhesives, realized at high temperature at high temperature The good adhesion performance and structural stability.
Patent Information
- Application Number
- CN202411409666.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The existing phenolic resin adhesives have problems such as oxidation ease, poor heat resistance, high curing temperature, slow curing speed, low production efficiency and large energy consumption, which limits their wide application in the field of high-tech.
Through 1,4-pyramlamine, phenol, formaldehyde, and formaldehyde are used to compose a modified phenolic resin, and the cross-linking with epoxy oxyladine is used to form epoxy-phenolic resin. At the same time, nano-nanocrobiography is modified by N-β- (amin ethyl)-γ-amino trivide trimethyloxine. It is used as a composite filler and adds armal adhesive to the composite filler.
Achieve the significant improvement of heat resistance, stability, and shear strength, maintain good adhesion performance and structural stability within the use temperature range, and solve the problem of decline in the performance of traditional adhesives at high temperature.
Smart Images

Figure BDA0005077644410000091 
Figure BDA0005077644410000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive preparation, in particular to a heat-resistant strong adhesive and a preparation method thereof. Background Art
[0002] Adhesives are an important industrial raw material and are widely used in the fields of automobile manufacturing, packaging, construction, furniture manufacturing, etc. In the early 20th century, the invention of phenolic resin marked the beginning of the era of synthetic adhesives. The subsequent development of high-performance synthetic resins such as epoxy resins, polyurethanes, and acrylates has greatly expanded the application range of adhesives. With the development of high-tech industries such as automobiles, electronics, and aerospace, improving temperature resistance, enhancing adhesive properties, and improving toughness and mechanical strength have become the development direction of synthetic resin adhesives.
[0003] Phenolic resin adhesives are prone to oxidation due to their phenolic hydroxyl and methylene structures, resulting in a brittle and hard adhesive layer that is easy to break, especially when the degree of crosslinking is insufficient, which shows poor heat resistance. In actual applications, phenolic resin adhesives also have problems such as high curing temperature, slow curing speed, low production efficiency, and high energy consumption, which limit their wider application. Phenolic resin has good compatibility. The toughness of phenolic resin is enhanced by composite modification of organic and inorganic substances, the heat resistance of the modified adhesive is improved, and better adhesive properties are given to meet the requirements of the high-tech field. Summary of the invention
[0004] The object of the present invention is to provide a heat-resistant strong adhesive and a preparation method thereof to solve the problems raised in the above background technology.
[0005] A heat-resistant strong adhesive comprises epoxy-phenolic resin and modified nano silicon dioxide.
[0006] Preferably, the epoxy-phenolic resin is prepared by co-condensing 1,4-naphthalene diamine, phenol and formaldehyde to obtain a modified phenolic resin, which is then cross-linked with epibromohydrin.
[0007] Preferably, the modified nano-silica is prepared by modification with N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0008] Preferably, the method for preparing the heat-resistant strong adhesive comprises the following specific steps:
[0009] (1) adding 0.3-0.6 mol of phenol and 0.2-0.3 mol of sodium hydroxide with a concentration of 20-30 wt% into a three-necked flask, stirring at 50 r / min for 10 min to make them uniform, and keeping the temperature at 35-45° C. for 20 min, adding 0.6 mol of formaldehyde and 0.1-0.3 mol of 1,4-naphthalenediamine into the three-necked flask to mix and react, the reaction temperature is 60° C., stirring at 80 r / min for 20 min, then raising the temperature to 75-80° C., adding 0.4 mol of formaldehyde and 0.1-0.2 mol of 1,4-naphthalenediamine, stirring at 100 r / min for 20 min to make them uniform, and keeping the temperature for 40 min to obtain a modified phenolic resin;
[0010] (2) After the modified phenolic resin is cooled to 70° C., epibromopropane is added, and 50-70 wt % of sodium hydroxide is added as a catalyst, the temperature of the system for the cross-linking reaction is raised to 85-90° C., and the mixture is stirred at 100-120 r / min for 20 min to mix evenly, and then the mixture is kept warm for 1 h to obtain an epoxy-phenolic resin;
[0011] (3) dispersing silica with a particle size of 20 nm in a 5-10 wt % ammonia water at a ratio of 1-1.5 mg / mL, adding N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, stirring at room temperature at a speed of 45-60 r / min for 12 h, centrifuging to obtain a solid, washing with deionized water and anhydrous ethanol, centrifuging 3-5 times, and drying in a 60° C. forced air oven for 2 h to obtain modified nano-silica;
[0012] (4) adding the modified nano-silica into the epoxy-phenolic resin, stirring at 80 rpm for 20 to 30 min at a constant temperature of 80 to 90 °C to mix evenly, refluxing at 95 to 100 °C for 45 to 60 min, cooling to 70 °C, degassing for 10 min, cooling to 30 to 40 °C, and discharging to obtain the heat-resistant strong adhesive.
[0013] Preferably, in the above step (1), the molar ratio of formaldehyde, 1,4-naphthalenediamine, phenol and sodium hydroxide is 1: 0.2-0.5: 0.3-0.6: 0.2-0.3.
[0014] Preferably, in the above step (2), the molar ratio of sodium hydroxide to modified phenolic resin is 1:0.14.
[0015] Preferably, in the above step (2), the molar ratio of the modified phenolic resin to epibromohydrin is 1:1.5-2.
[0016] Preferably, in the above step (3), the mass ratio of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane to nano-silicon dioxide is 1 to 1.2:2.
[0017] Preferably, in the above step (3), the centrifugation condition is 8000-10000 r / min, and the centrifugation time is 10 min.
[0018] Preferably, in the above step (4), the mass ratio of the modified nano-silica to the modified epoxy-phenolic resin is 1:45-55.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The present invention prepares a heat-resistant strong adhesive with modified phenolic resin and epoxy group-containing epibromohydrin to achieve excellent heat resistance, stability and shear strength.
[0021] Firstly, the present invention prepares the modified phenolic resin by co-condensing 1,4-naphthalenediamine with phenol and formaldehyde. The 1,4-naphthalenediamine has a naphthalene ring and two amino functional groups. The naphthalene ring provides good stability. The main chain of the phenolic resin adhesive introduces an aromatic amine structure with good thermal stability, so that the glass transition temperature is increased, thereby improving the heat resistance of the present invention, so as to maintain good bonding performance and structural stability within the use temperature range.
[0022] Secondly, epoxy-phenolic resin is generated by reacting epibromopropane with modified phenolic resin in the presence of an alkaline catalyst. The epoxy group can undergo a cross-linking reaction with the phenolic hydroxyl group. The phenolic hydroxyl group acts as a nucleophilic reagent to insert its oxygen atom into the epoxy ring. After the ring is opened, a new CO bond is formed, forming a cross-linking point between the molecules, and converting the original linear or branched molecular structure into a three-dimensional network structure. At the same time, based on the nucleophilic addition reaction between amine compounds and epoxy groups, 1,4-naphthalenediamine can undergo a ring-opening reaction with the epoxy group of the epoxy compound to form a new chemical bond. Thus, the epoxy-phenolic resin has a more stable network structure, and the shear strength and peel strength of the invention are improved; the nano-silicon dioxide is modified by using N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, which, as a composite filler with rich amino groups on the surface, improves the dispersibility of the nano-silicon dioxide in the resin and forms a more complex three-dimensional network structure by ring-opening cross-linking with epoxy groups; and the alkoxy part of the modifier is hydrolyzed to generate a silanol group, forming a stable Si-O-Si bond, thereby improving the overall heat resistance and structural stability of the invention. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the heat-resistant strong adhesives prepared in the following examples and comparative examples are as follows:
[0025] 180° peel strength: The adhesives prepared in the examples and comparative examples were coated on the surface of a PI film with a width of 25 mm and a length of 200 mm. After bonding with metal, the peel strength of the adhesive was tested according to standard GB / T2790. The tensile speed of the universal electronic tensile testing machine was 200 mm / min. The average value was calculated after 5 measurements.
[0026] Heat resistance: The adhesives prepared in the examples and comparative examples were coated on the surface of a PI film with a width of 25 mm and a length of 200 mm. After bonding with the metal, the test pieces for peel strength testing were placed in an oven at 250°C. After 48 hours, they were taken out and cooled. The peel strength of the adhesive was tested according to standard GB / T2790. The tensile speed of the universal electronic tensile testing machine was 200 mm / min. The test pieces were measured 5 times and the average value was calculated.
[0027] Example 1; (1) 0.3 mol of phenol and 0.2 mol of sodium hydroxide with a concentration of 20 wt% were added to a three-necked flask, stirred at 50 r / min for 10 min, and kept warm at 40°C for 20 min. 0.6 mol of formaldehyde and 0.1 mol of 1,4-naphthalenediamine were added to the three-necked flask to mix and react. The reaction temperature was 60°C, stirred at 80 r / min for 20 min, and then the temperature was raised to 75°C. 0.4 mol of formaldehyde and 0.2 mol of 1,4-naphthalenediamine were added, stirred at 100 r / min for 20 min, and kept warm for 40 min to obtain a modified phenolic resin;
[0028] (2) After the modified phenolic resin is cooled to 70° C., epibromopropane is added, and 50 wt % sodium hydroxide is added as a catalyst, the temperature of the system for the cross-linking reaction is raised to 85° C., and the mixture is stirred at 100 r / min for 20 min to be evenly mixed, and then the mixture is kept warm for 1 h to obtain an epoxy-phenolic resin;
[0029] (3) dispersing silica with a particle size of 20 nm in a 5 wt % ammonia water at a ratio of 1 mg / mL, adding N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, stirring at room temperature at 45 r / min for 12 h, centrifuging to obtain a solid, washing with deionized water and anhydrous ethanol, centrifuging 3-5 times, and drying in a 60° C. forced air oven for 2 h to obtain modified nano-silica;
[0030] (4) adding the modified nano-silica into the epoxy-phenolic resin, stirring at 80 rpm for 20 min at a constant temperature of 80° C. to mix evenly, refluxing at 95° C. for 45 min, cooling to 70° C. and degassing for 10 min, then cooling to 35° C. to obtain the heat-resistant strong adhesive.
[0031] Example 2: (1) 0.5 mol of phenol and 0.25 mol of 24 wt% sodium hydroxide were added to a three-necked flask, stirred at 50 r / min for 10 min, and kept warm at 40°C for 20 min. Then, 0.6 mol of formaldehyde and 0.15 mol of 1,4-naphthalenediamine were added to the three-necked flask to mix and react. The reaction temperature was 60°C, stirred at 80 r / min for 20 min, and then the temperature was raised to 75°C. 0.4 mol of formaldehyde and 0.2 mol of 1,4-naphthalenediamine were added, stirred at 100 r / min for 20 min, and kept warm for 40 min to obtain a modified phenolic resin.
[0032] (2) After the modified phenolic resin is cooled to 70° C., epibromopropane is added, and 60 wt % sodium hydroxide is added as a catalyst, the temperature of the system for the cross-linking reaction is raised to 90° C., and the mixture is stirred at 120 r / min for 20 min to be evenly mixed, and then the mixture is kept warm for 1 h to obtain an epoxy-phenolic resin;
[0033] (3) dispersing silica with a particle size of 20 nm in ammonia water at a ratio of 1.4 mg / mL in a concentration of 8 wt %, adding N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, stirring at room temperature at a speed of 50 r / min for 12 h, centrifuging to obtain a solid, washing with deionized water and anhydrous ethanol, centrifuging 3-5 times, and drying in a 60° C. forced air oven for 2 h to obtain modified nano-silica;
[0034] (4) adding the modified nano-silica into the epoxy-phenolic resin, stirring at 80 rpm for 30 min at a constant temperature of 85° C. to mix evenly, refluxing at 95° C. for 60 min, cooling to 70° C. and degassing for 10 min, then cooling to 35° C. to obtain the heat-resistant strong adhesive.
[0035] Example 3; (1) 0.6 mol of phenol and 0.3 mol of sodium hydroxide with a concentration of 30 wt% were added to a three-necked flask, stirred at 50 r / min for 10 min, and kept warm at 45°C for 20 min. 0.6 mol of formaldehyde and 0.3 mol of 1,4-naphthalenediamine were added to the three-necked flask to mix and react. The reaction temperature was 60°C. After stirring at 80 r / min for 20 min, the temperature was raised to 80°C, 0.4 mol of formaldehyde and 0.1 mol of 1,4-naphthalenediamine were added, and the mixture was stirred at 100 r / min for 20 min. After that, the mixture was kept warm for 40 min to obtain a modified phenolic resin.
[0036] (2) After the modified phenolic resin is cooled to 70° C., epibromopropane is added, and 70 wt % sodium hydroxide is added as a catalyst, the temperature of the system for the cross-linking reaction is raised to 90° C., and the mixture is stirred at 120 r / min for 20 min to be evenly mixed, and then the mixture is kept warm for 1 h to obtain an epoxy-phenolic resin;
[0037] (3) dispersing silica with a particle size of 20 nm in a 10 wt % ammonia water at a ratio of 1.5 mg / mL, adding N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, stirring at room temperature at 60 r / min for 12 h, centrifuging to obtain a solid, washing with deionized water and anhydrous ethanol, centrifuging 3-5 times, and drying in a 60° C. forced air oven for 2 h to obtain modified nano-silica;
[0038] (4) adding the modified nano-silica into the epoxy-phenolic resin, stirring at 80 rpm for 30 min at a constant temperature of 90° C. to mix evenly, refluxing at 100° C. for 60 min, cooling to 70° C. and degassing for 10 min, then cooling to 40° C. to obtain the heat-resistant strong adhesive.
[0039] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: 0.5 mol of phenol and 0.25 mol of sodium hydroxide with a concentration of 10wt% are added to a three-necked flask, stirred at 50r / min for 10min, and kept warm at 40°C for 20min. Then, 0.6 mol of formaldehyde and 0.1 mol of 1,4-naphthalenediamine are added to the three-necked flask to mix and cause a condensation reaction. The reaction temperature is 60°C, and the reaction is stirred at 80r / min for 20min. Then, the temperature is raised to 75°C, 0.4 mol of formaldehyde is added, and the mixture is stirred at 100r / min for 20min. After mixing, the mixture is kept warm for 40min to obtain a modified phenolic resin. The remaining steps are the same as those in Example 2.
[0040] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: 0.5 mol of phenol and 0.25 mol of sodium hydroxide with a concentration of 24wt% are added to a three-necked flask, stirred at 50r / min for 10min, and kept warm at 40°C for 20min. Then, 0.5 mol of formaldehyde and 0.15 mol of 1,4-naphthalenediamine are added to the three-necked flask to mix and cause a condensation reaction. The reaction temperature is 60°C, and the reaction is stirred at 80r / min for 20min. Then, the temperature is raised to 75°C, 0.2 mol of 1,4-naphthalenediamine is added, and the mixture is stirred at 100r / min for 20min. After mixing, the mixture is kept warm for 40min to obtain a modified phenolic resin. The remaining steps are the same as those in Example 2.
[0041] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: after the modified phenolic resin is cooled to 70°C, epibromopropane is added, and 24wt% sodium hydroxide is added as a catalyst, the temperature of the system where the cross-linking reaction occurs is raised to 75°C, stirred at 50r / min for 20min to mix evenly, and then kept warm for reaction for 1h to obtain epoxy-phenolic resin; the remaining steps are the same as Example 2.
[0042] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that there is no step (3), and step (4) is changed to: adding nano-silicon dioxide with a particle size of 20 nm to the epoxy-phenolic resin, stirring at 80 r / min for 30 min at a constant temperature of 85°C to mix, reflux at 95°C for 60 min, cool to 70°C, degas for 10 min, and then cool to 35°C to obtain the heat-resistant strong adhesive; the remaining steps are the same as Example 2.
[0043] Effect example
[0044] Table 1 below shows the performance analysis results of the heat-resistant strong adhesives of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0045] Table 1
[0046]
[0047]
[0048] From the comparison of the experimental data of the 180° peel strength of the embodiment and the comparative example and the 180° peel strength after 48 hours of high temperature, it can be found that the present invention prepares the modified phenolic resin by co-condensing 1,4-naphthalene diamine with phenol and formaldehyde, and introduces a heat-stable aromatic amine structure on the main chain of the phenolic resin adhesive, thereby increasing the glass transition temperature, thereby improving the heat resistance of the present invention, so as to maintain good bonding performance and structural stability within the use temperature range; the phenolic resin is modified by epibromohydrin, and the phenolic hydroxyl group is used as a nucleophilic reagent to insert its oxygen atom into the epoxy ring, and a new CO bond is formed after the ring is opened, forming a cross-linking point between molecules, and the original linear or branched molecular structure is converted into a three-dimensional network structure, thereby improving the shear strength and adhesiveness of the adhesive. Adhesive strength; at the same time, based on the nucleophilic addition reaction between the amine compound and the epoxy group, 1,4-naphthalene diamine can undergo a ring-opening reaction with the epoxy group of the epoxy compound to form a new chemical bond, so that the epoxy-phenolic resin has a more stable network structure, further improving the shear strength and peel strength of the present invention; the nano-silica modified with N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane is used as a composite filler with rich amino groups on the surface, while improving the dispersibility of the nano-silica in the resin, and forming a more complex three-dimensional network structure through ring-opening cross-linking with the epoxy group, and the alkoxy part of the modifier is hydrolyzed to generate a silanol group to form a stable Si-O-Si bond, thereby improving the overall heat resistance and structural stability of the present invention.
[0049] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A heat-resistant strong adhesive, characterized in that: The heat-resistant strong adhesive comprises epoxy-phenolic resin and modified nano silicon dioxide.
2. A heat-resistant strong adhesive according to claim 1, characterized in that: The epoxy-phenolic resin is prepared by co-condensing 1,4-naphthalene diamine, phenol and formaldehyde to obtain a modified phenolic resin, which is then cross-linked with epibromohydrin to obtain the modified phenolic resin.
3. A heat-resistant strong adhesive according to claim 1, characterized in that: The modified nano silicon dioxide is prepared by modification with N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
4. A method for preparing a heat-resistant strong adhesive, characterized in that: The method comprises the following preparation steps: (1) adding 0.3-0.6 mol of phenol and 0.2-0.3 mol of sodium hydroxide with a concentration of 20-30 wt% into a three-necked flask, stirring at 50 r / min for 10 min to make them uniform, and keeping the temperature at 35-45° C. for 20 min, adding 0.6 mol of formaldehyde and 0.1-0.3 mol of 1,4-naphthalenediamine into the three-necked flask to mix and react, the reaction temperature is 60° C., stirring at 80 r / min for 20 min, then raising the temperature to 75-80° C., adding 0.4 mol of formaldehyde and 0.1-0.2 mol of 1,4-naphthalenediamine, stirring at 100 r / min for 20 min to make them uniform, and keeping the temperature for 40 min to obtain a modified phenolic resin; (2) After the modified phenolic resin is cooled to 70° C., epibromopropane is added, and 50-70 wt % of sodium hydroxide is added as a catalyst, and the temperature of the system where the cross-linking reaction occurs is raised to 85-90° C. Stir at 100-120 r / min for 20 min to mix evenly, then keep warm and react for 1 h to obtain epoxy-phenolic resin; (3) dispersing silica with a particle size of 20 nm in a 5-10 wt % ammonia water at a ratio of 1-1.5 mg / mL, adding N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, stirring at room temperature at a speed of 45-60 r / min for 12 h, centrifuging to obtain a solid, washing with deionized water and anhydrous ethanol, centrifuging 3-5 times, and drying in a 60° C. forced air oven for 2 h to obtain modified nano-silica; (4) adding the modified nano-silica into the epoxy-phenolic resin, stirring at 80 rpm for 20 to 30 min at a constant temperature of 80 to 90 °C to mix evenly, refluxing at 95 to 100 °C for 45 to 60 min, cooling to 70 °C, degassing for 10 min, cooling to 30 to 40 °C, and discharging to obtain the heat-resistant strong adhesive.
5. The method for preparing a heat-resistant strong adhesive according to claim 4, characterized in that: In the step (1), the molar ratio of formaldehyde, 1,4-naphthalenediamine, phenol and sodium hydroxide is 1: 0.2-0.5: 0.3-0.6: 0.2-0.
3.
6. The method for preparing a heat-resistant strong adhesive according to claim 4, characterized in that: In the step (2), the molar ratio of sodium hydroxide to modified phenolic resin is 1:0.
14.
7. The method for preparing a heat-resistant strong adhesive according to claim 4, characterized in that: In the step (2), the molar ratio of the modified phenolic resin to epibromohydrin is 1:1.5-2.
8. The method for preparing a heat-resistant strong adhesive according to claim 4, characterized in that: In the step (3), the mass ratio of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane to nano-silicon dioxide is 1-1.2:
2.
9. The method for preparing a heat-resistant strong adhesive according to claim 4, characterized in that: The centrifugal condition in step (3) is 8000-10000 r / min, and the centrifugal time is 10 min.
10. The method for preparing a heat-resistant strong adhesive according to claim 4, characterized in that: In the step (4), the mass ratio of the modified nano-silica to the modified epoxy-phenolic resin is 1:45-55.
Citation Information
Patent Citations
Preparation method of nano silicon dioxide modified phenolic resin
CN104961872A
Preparation method of surface-modified nano silicon dioxide modified phenolic resin
CN109880283A
Nano-silica modified water-based phenolic resin and preparation method thereof
CN112708087A
Heat-resistant silicon dioxide modified phenolic resin high-strength coating and preparation method thereof
CN113845814A
Processing technology of phenolic resin-based high-temperature-resistant circuit board
CN115819920A